The Activity Concentration of Radionuclides (226Ra, 232Th and 40K) in Soil Samples and Associated Health Hazards in Natore, Kushtia and Pabna District of Bangladesh (Journal of Bangladesh Academy of Sciences, 2020)
The study has been carried out to measure the activity concentration of natural and anthropogenic radionuclides in fifteen(15) soil samples of Natore, Kushtia and Pabna district, which are around the 30 km peripheral area of Rooppur Nuclear Power Plant, by gamma ray spectrometry system using a High Purity Germanium (HPGe) detector. It is found that the activity concentration of 226Ra, in the collected sample was from 3.52 Bq/kg to 28.5 Bq/kg with the average value of 12.42 Bq/kg. For 232Th, the range was from 4.18 Bq/kg to 34.5 Bq/kg with the average value of 12.6 Bq/kg. Finally, the activity concentration of 40K, in the collected sample was in the range of 84 Bq/kg to 345 Bq/kg, and the average value was 198.9 Bq/kg. The absorbed dose rate (D) was found to be in the range of 4.59 nGy/h to 40.93 nGy/h with the mean value 21.3 nGy/h. The annual effective dose (E) was in the range of 0.006 mSv/yr to 0.152 mSv/yr with an average of 0.033 mSv/yr. The radium equivalent activity was in the range from 10.02 Bq/kg to 89 Bq/kg with an average of 44.99 Bq/kg. The external hazard index (Hex) was found to be in the range of 0.027 to 0.242 with the mean value of 0.121 and the internal hazard index (Hin) was found to be in the range of 0.044 to 0.302 with the mean value of 0.156. All the values are much below the recommended limit by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR), 35 Bq/kg for 226Ra, 30 Bq/kg for 232Th and 400 Bq/kg for 40K. According to international and national regulation, the annual dose to members of the public, 1 mSvy-1 and Hex & Hin must be lower than unity. Moreover, no artificial radioactivity was found in the soil samples of this study area. This research concludes that the found values are within the permissible limits as required by the Nuclear Safety and Radiation Control(NSRC) Rules-1997 of Bangladesh and International Atomic Energy Agency(IAEA) Safety Standards- General Safety Requirements (GSR): Part-3.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 169-180, 2019